College Student’s Financial Well-Being on Java Island: The Role of Financial Literacy, Financial Behavior, and Financial Socialization - Nony Kezia Marchyta; Matthew Lay; Adhityawati Kusumawardhani (International Journal of Organizational Behavior and Policy, 2024)
After graduating from college, a student's financial situation is critical since it impacts their general level of contentment with life. This study used financial behavior among university students on Java Island to investigate the impact of financial socialization and literacy on financial well-being. This kind of study uses a non-probability sampling method and quantitative methods, involving 134 students in Java Island data processing procedures with Smart PLS. The findings revealed that financial socialization and financial literacy are favorably related to financial well-being. Financial literacy and financial socialization positively affected both financial behavior and financial well-being. Financial conduct acts as a mediating variable between financial well-being, financial literacy, and financial socialization, which both have a favorable impact.